Chapter Checklist of amphipods of italian seas: baseline for monitoring biodiversity - Jacofano, Davide; Krapp, Traudl; Badalucco, Antonina; Auriemma, Rocco; Bonifazi, Andrea; Cimmaruta, Roberta; De Mattahaeis, Elvira; Di Camillo, Cristina; Esposito, Valentina; Latella, Leonardo; Lattanzi, Loretta; lezzi, marco; et al. (Firenze University Press, 2025)
This preliminary study presents an updated checklist of amphipod crustaceans inhabiting Italian seas and provides valuable insights into their diversity, distribution, and ecological traits. By combining existing literature with unpublished data, we were able to record 500 species in Italian waters. The analyses revealed a significant increase in the number of amphipod species documented in the Country, primarily due to intensified research efforts and the introduction of non-native species. This study highlights the importance of ongoing monitoring and research to assess marine biodiversity. Future efforts should prioritize understudied groups, such as planktonic species, and those living in deep-sea marine environments.